1999
DOI: 10.1093/oxfordjournals.aje.a009975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticide Exposure on Time to Pregnancy, Results of a Multicenter Study in France and Denmark

Abstract: The aim of this study was to determine whether there was a relation between male exposure to pesticides and the amount of time needed to conceive (time to pregnancy) for farmers and agricultural workers in France and Denmark. The authors used retrospective studies to compare the time to pregnancy of couples in which the man was exposed to pesticides during the year before the birth of their youngest child with that of couples in which the man was not exposed. In 1995 and 1996, the authors studied 362 French ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 20 publications
2
30
0
1
Order By: Relevance
“…Exposure of the father to pesticides during the preconception period or prior can also increase the risk of having anencephalic child [81]. Men engaged in agricultural practices adopting use of pesticides are at increased risk of fetal death from congenital anomalies, particularly where pesticides are used massively [82]. Paternal pesticide exposure has been otherwise reported to decrease fertilizing ability of sperm in those seeking IVF treatment [83].…”
Section: Pesticides and Other Polychlorinated Hydrocarbonsmentioning
confidence: 99%
“…Exposure of the father to pesticides during the preconception period or prior can also increase the risk of having anencephalic child [81]. Men engaged in agricultural practices adopting use of pesticides are at increased risk of fetal death from congenital anomalies, particularly where pesticides are used massively [82]. Paternal pesticide exposure has been otherwise reported to decrease fertilizing ability of sperm in those seeking IVF treatment [83].…”
Section: Pesticides and Other Polychlorinated Hydrocarbonsmentioning
confidence: 99%
“…Some other pesticides [ie, 2,4-dichlorophenoxyacetic acid (2,4-D), ethylene dibromide (EDB), chlordecone (Kepone TM ), and carbaryl] have also been shown to cause adverse effects on semen quality (2)(3). A Dutch study observed decreased fecundability among highly exposed fruit growers as compared with that of workers with low exposure (4), but three other studies found no association between exposure to pesticide and male fecundability (5)(6)(7). All in all, data on the effects of pesticide exposure on male fertility are scarce and difficult to compare due to exposure heterogeneity.…”
mentioning
confidence: 99%
“…Although many animal studies have been performed on the reproductive toxicity of pesticides (1,(3)(4)(5)(6) and pregnancy outcome has been evaluated in several human studies (7)(8)(9)(10)(11)(12)(13)(14)(15), effects on human fertility have only recently been considered (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). For many pesticides, no information is available, and the majority of epidemiologic studies to date pertain to pesticides that are no longer used.…”
mentioning
confidence: 99%
“…For many pesticides, no information is available, and the majority of epidemiologic studies to date pertain to pesticides that are no longer used. Several studies investigated male workers only (16)(17)(18)(19), while the results from a study in Finland indicated reduced fertility among wives of Finnish greenhouse workers exposed to pesticides (20).…”
mentioning
confidence: 99%